2013
DOI: 10.1007/978-3-642-40564-8_30
|View full text |Cite
|
Sign up to set email alerts
|

Combining Equilibrium Logic and Dynamic Logic

Abstract: We extend the language of here-and-there logic by two kinds of atomic programs allowing to minimally update the truth value of a propositional variable here or there, if possible. These atomic programs are combined by the usual dynamic logic program connectives. We investigate the mathematical properties of the resulting extension of equilibrium logic: we prove that the problem of logical consequence in equilibrium models is EXPTIME complete by relating equilibrium logic to dynamic logic of propositional assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…We believe that epistemic here-and-there logic EHT provides a suitable basis for further extensions of answer-set programs with modal concepts, which is a research avenue that has recently arisen some interest specifically for extensions by temporal [42][43][44][45][46][47] and dynamic [48] concepts. A first step could be the extension from single-agent epistemic logic to multi-agent epistemic logic.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that epistemic here-and-there logic EHT provides a suitable basis for further extensions of answer-set programs with modal concepts, which is a research avenue that has recently arisen some interest specifically for extensions by temporal [42][43][44][45][46][47] and dynamic [48] concepts. A first step could be the extension from single-agent epistemic logic to multi-agent epistemic logic.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the embedding of CL-PC that we have recalled in Sect. 3.5, the central role of DL-PA is confirmed by DL-PA accounts of update and revision operations [54], belief merging operations [63], abstract argumentation theories and their modification [33], and answer-set programs and their modification [36]; moreover, its epistemic extension, public announcement logic with assignments, solves the epistemic frame problem [114,115]. As to logics with epistemic operators, we have recalled that S5 is inadequate as a logic of knowledge and should be replaced by S4.2; furthermore, we have shown that the definition of common knowledge by means of the Greatest Fixpoint Axiom GFP(CK J ) is at least questionable.…”
Section: Summary and Research Challengesmentioning
confidence: 89%
“…Its applicability to update and revision operations, planning tasks, argumentation theory and answer-set programming has been demonstrated recently [33,36,54,62]. In the rest of the section we show that it captures a logic of ability.…”
Section: Reiter's Solution To the Frame Problemmentioning
confidence: 99%
“…An epistemic interpretation I is called an Sworld view of an ELP Π iff I = AS (Π I S ) and I = ∅. Various semantics S have been defined over the years and most of them can be characterized by reducts Π I S , either over sets of interpretations (as above) or over the set of elit(Π) that are satisfied by I (Kahl 2014;del Cerro, Herzig, and Su 2015;Shen and Eiter 2016;Son et al 2017;Kahl and Leclerc 2018;Faber, Morak, and Woltran 2019;Morak 2019;Cabalar, Fandinno, and del Cerro 2020). A concise summary can be found in (Leclerc and Kahl 2018).…”
Section: Preliminariesmentioning
confidence: 99%
“…e.g. (Gelfond 2011;Truszczynski 2011;Kahl 2014;del Cerro, Herzig, and Su 2015;Shen and Eiter 2016;Son et al 2017;Kahl and Leclerc 2018;Faber, Morak, and Woltran 2019;Morak 2019)), with refinements of the semantics and proposals of new language features. Further, the development of efficient solving systems is underway with several efficient systems now available (Kahl et al 2015;Son et al 2017;Bichler, Morak, and Woltran 2020).…”
Section: Introductionmentioning
confidence: 99%